Novel highly-multiplexed AmpliSeq targeted assay for Plasmodium vivax genetic surveillance use cases at multiple geographical scales - Kattenberg, Johanna Helena; Nguyen, Hong Van; Nguyen, Hieu Luong; Sauve, Erin; Nguyen, Ngoc Thi Hong; Chopo-Pizarro, Ana; Trimarsanto, Hidayat; Monsieurs, Pieter; Guetens, Pieter; Nguyen, Xa Xuan; Esbroeck, Marjan Van; Auburn, Sarah; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Many countries co-endemic for Plasmodium vivax and Plasmodium falciparum that are moving towards malaria elimination in the next 5-10 years are making minimal progress with reducing P. vivax cases. Residual P. vivax can be challenging to eliminate due to subpatent and asymptomatic infections and hidden reservoirs. Although the power of genetic surveillance tools has been acknowledged widely, there is an urgent need in malaria endemic countries for feasible and cost-effective tools to implement in national malaria control programs that can generate evidence to guide malaria control and elimination strategies. To bridge the gap between research and implementation, several genetic surveillance applications (‘use cases’) have been identified to align research, technology development, and public health efforts. Genetic tools can quantify malaria importation risk, characterize changing transmission intensity and guide malaria control by distinguishing imported vs. indigenous cases and sources of reintroduction. In addition, molecular markers associated with drug resistance can be reliable predictors of treatment responses. Here we present a new highly-multiplexed deep sequencing assay (Pv AmpliSeq). The assay targets the 33-SNP vivaxGEN-geo panel for country-level classification, and a 42-SNP within-country barcode for analysis of parasite dynamics and 11 putative drug resistance genes in a highly multiplexed NGS protocol with easy workflow, applicable for many different genetic surveillance use cases. The Pv AmpliSeq assay was validated using: 1) isolates from travelers and migrants in Belgium, and 2) routine collections of the national malaria control program at sentinel sites in Vietnam. The assay achieved good spatial specificity for between-country prediction of origin, and high resolution for within-country diversity and gene flow analysis in Vietnam. Many variants were detected in (putative) drug resistance genes, with different haplotypes predominant in pvmdr1 and pvcrt genes, in different provinces in Vietnam. Our approach performed well in geographically differentiating isolates at multiple spatial scales, detecting variants in putative resistance genes, and can be easily adjusted to suit the needs for other settings. We prioritize making this tool available to researchers and control programs in endemic countries to increase ownership and ensure data usage for decision-making and malaria policy.